2018
DOI: 10.1111/voxs.12433
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a patient blood management programme in Brazil: challenges and implications for developing countries

Abstract: Background Patient blood management (PBM) programmes have the intention of promoting the rational use of blood, relying on up‐to‐date medical‐scientific evidence in a multidisciplinary approach, where the patient is the main focus of transfusion decisions. These programmes not only increase patient safety levels, but they also have the potential of lowering hospital costs. The aim of this study was to describe the implementation of a PBM programme at a University hospital in Brazil. Study design and methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The latter are associated with fewer guideline deviations, by a more highly transfusion-educated physician and frequently after a discussion with the blood bank team. The RBC transfusions are ordered by any physician, with a higher propensity for out-of-protocol requests 11 …”
Section: Discussionmentioning
confidence: 99%
“…The latter are associated with fewer guideline deviations, by a more highly transfusion-educated physician and frequently after a discussion with the blood bank team. The RBC transfusions are ordered by any physician, with a higher propensity for out-of-protocol requests 11 …”
Section: Discussionmentioning
confidence: 99%
“…Restrictive trigger has been used by many centers to reduce the allogeneic perioperative transfusion for their patients. 10,11 However, even if restrictive trigger is used with less units transfused, blood transfusion is also associated with a worse postoperative outcome in surgical and critically ill patients. A large study that compared the effect of red cell transfusion showed higher rates of morbidity and mortality in patients receiving one unit of red cells compared with patients who were not transfused.…”
Section: Discussionmentioning
confidence: 99%
“…In less developed health systems, such as the Brazilian health system, few isolated initiatives can be identified. 11 This study is part of a larger project to implement a PBM program in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Benites et al reported a positive experience implementing a PBM program in a university hospital. 8 According to the authors, “The project was promptly approved by the hospital Board due to the relevance of the proposal, which required few financial resources, as the project is mainly based on the reorganization of workflows”.…”
Section: Patient-centered Carementioning
confidence: 99%